Effects of enrofloxacin and povidone‐iodine on immunity, the intestinal microbiome and transcriptome of juvenile grass carp ( Ctenopharyngodon idella ) - Zhilong Chen; Lixin Ma; Sien Chen; Yao Huang; Zhendong Qin; Li Lin; Fei Shi (Journal of Fish Biology, 2025)
Gut microbiota stability is crucial for maintaining fish health. In aquaculture, antibiotics and disinfectants are frequently used to manipulate the host gut microbiota, but the combined effects on asymptomatic fish remain unclear. We investigated the effects of single and combined treatments with antibiotics and disinfectants on grass carp ( Ctenopharyngodon idella ) gut health, immune response, microbiome dynamics and transcriptome profile. In a 2‐week trial, grass carp were exposed to enrofloxacin (10 mg/kg) in the basal diet or povidone‐iodine (0.05 mg/L) in fresh water. A 14‐day treatment led to significant oxidative stress, as indicated by reduced catalase and total superoxide dismutase activities. Digestive enzyme activities, including amylase and lipase, were also significantly suppressed. Gut microbiota diversity decreased, with notable shifts in dominant bacterial phyla, including reduced abundances of Firmicutes and Bacteroidetes and increased Proteobacteria and Fusobacteria. Transcriptomic analysis revealed downregulation of immune‐related pathways, including those linked to IgA production, and suppression of key immune‐related genes, such as major histocompatibility complex 2 ( MHC2 ) and tumour necrosis factor alpha ( TNF‐α ). Histopathological analysis showed damaged intestinal villi, increased goblet cell numbers and significant apoptosis in intestinal epithelial cells, as confirmed by terminal deoxynucleotidyl transferase (TdT) dUTP Nick‐End Labeling (TUNEL) staining and upregulation of caspase ‐3, caspase ‐8 and caspase ‐9. These findings demonstrate that enrofloxacin and povidone‐iodine disrupt gut microbiota balance, impair mucosal immunity and induce apoptosis in grass carp.